Quantification of patellar tendon strain and opportunities for personalized tendon loading during back squats - K. Weidlich; F. Mersmann; T. Domroes; A. Schroll; S. Bohm; A. Arampatzis (Scientific Reports, 2023)
Abstract Tendon strain during exercise is a critical regulatory factor in tendon adaptive responses and there are indications for an optimal range of strain that promotes tendon adaptation. Back squats are used to improve patellar tendon properties in sport and clinical settings. To date, the operating patellar tendon strain during back squats is unknown and current recommendations for individual exercise loading are based on the one repetition maximum (1RM). Here, we quantified patellar tendon strain during loaded back squats at 40, 60 and 80% of the 1RM and during maximum isometric knee extension contractions (MVC) using ultrasonography. Kinematics, ground reaction forces and muscle electromyographic activity were also recorded. Additionally, maximum tendon strain during the MVC and the percentage of 1RM were used as explanatory variables to estimate the individual patellar tendon strain during the squats. Strain increased with increasing 1RM loading (4.7 to 8.2%), indicating that already medium-loading back squats may provide a sufficient stimulus for tendon adaptation. The individual variability was, however, too high to generalize these findings. Yet, there was a high agreement between the individually estimated and measured patellar tendon strain (R2 = 0.858) during back squats. We argue that this approach may provide new opportunities for personalized tendon exercise.